Bonding from Womb: A Mixed Method Study of Pregnant Women’s Knowledge, Attitude, and Experiences on Fetal Movement - Widiasih, Restuning; Khoirunnisa, Khoirunnisa; Mamuroh, Lilis; Al Baihaqi, Windy Natasya; Popoola, Tosin (Nurse Media Journal of Nursing, 2026)
Background: Fetal movement is an important indicator of fetal life and well-being and contributes to maternal–fetal bonding. However, evidence on pregnant women’s knowledge, attitudes, behaviors, self-efficacy, and experiences in self-monitoring fetal well-being remains limited.Purpose: This study aimed to comprehensively examine pregnant women’s knowledge, attitudes, behaviors, self-efficacy, and experiences related to fetal movement monitoring.Methods: A mixed-methods study with a concurrent triangulation design was conducted. Quantitative and qualitative data were collected simultaneously through a survey of 216 respondents from two districts and interviews with 18 participants drawn from the survey pool. Comparative analysis was used to assess differences in knowledge, attitudes, behaviors, and self-efficacy between the two districts using the Mann–Whitney test for survey data, while thematic analysis was applied to the interview data.Results: Overall, the majority of pregnant women demonstrated low knowledge (64.4%), negative self-monitoring behaviors (52.7%), and low self-efficacy (56.0%), while attitudes toward fetal movement self-observation were slightly more favorable (53.7%). Statistical analysis indicated significant differences in knowledge, attitudes, and behaviors related to fetal movement self-observation (p < .05), whereas self-efficacy was not statistically significant (p > .05). Thematic analysis identified four themes: (1) Bonding since in the womb; (2) Emotional responses; (3) Actions when sensing abnormalities; and (4) Culture and beliefs.Conclusion: The findings suggest that mothers and fetuses form a strong emotional bond from the womb, as reflected in maternal experiences and behaviors. There is a need for nursing interventions in fetal monitoring, particularly to improve pregnant women’s knowledge, attitudes, behaviors, and self-efficacy. Furthermore, this study strengthens the evidence base for maternity nursing practice, enabling nurses and midwives to design targeted educational and monitoring interventions that promote pregnant women’s autonomy in observing fetal health and responding appropriately to early warning signs.